Stress-induced a/b compound twins redistribution in 10M Ni-Mn-Ga martensite. (15th January 2020) - Saren, A.; Sozinov, A.; Kustov, S.; Ullakko, K.
Abstract: Slight orthorhombic and monoclinic distortion of approximately tetragonal lattice in five-layered modulated (10M) martensite of Ni-Mn-Ga leads to the formation of laminates consisting of a/b compound twins. Here, we present the first direct optical observation and x-ray diffraction confirmation of the stress-induced redistribution of a/b twins of ~1–15 μm in size. We demonstrate that a/b twins are highly mobile, exhibiting twinning stress as low as 0.1 MPa, which is comparable to the twinning stress of Type 2 a/c twin boundaries. We assume that a local rearrangement of the a/b laminate may occur during the motion of a/c twin boundaries. Graphical abstract: Unlabelled Image